(untitled) (Journal of the College of Basic Education, 2023)
The current study was conducted on a group of patients (25 males and 25 females) who showed a significant increase (P<0.05) in blood pressure, and an increase in blood viscosity by examining (PCV%) in order to find out the effect of eating celery at low and medium levels. And a lot, as well as smoking on some blood parameters (Hb gm%, PCV%) and blood pressure, both high (HP) and low (LP).The patients were divided into five age groups (20-29), (30-39), (40-49), (50-59) and (60-69) years. Each group contained ten patients (5 males and 5 females). A control group of ten non-smokers (5 males and 5 females).The results showed the role of celery in reducing blood pressure in all the above age groups, compared with the age group (60-69) years, which was characterized by high blood pressure (Hb gm%) and (PCV%). A significant increase (P<0.05) was observed in hemoglobin. Blood, (Hb gm%) and (PCV%) and blood pressure in subjects who smoked one pack, two packs and three packs in comparison with the control group.The consumption of celery in the low consumption group showed a significant decrease (P<0.05) in the rates of (Hb gm%), (PCV%) and blood pressure compared to the medium and high consumption groups, and the effect of gender was significant (P<0.05) on blood parameters and blood pressure in The female group compared to the male group.We conclude from this research that eating celery has an important role in reducing blood pressure in different age groups, especially in patients with high blood pressure in this study compared to the age group (60-69 years) as well as in groups of smokers, thus reducing the negative effect of smoking that works On high blood pressure, and this may be due to the presence of a substance (Butyl - phthalide) (3nB) in celery, which dilates blood vessels, which contributes to lowering blood pressure.